Single-chain folding and self-assembling of amphiphilic polyethyleneglycol-modified fluorinated styrene homopolymers in water solution. (28th September 2021) - Guazzelli, Elisa; Masotti, Elena; Calosi, Matteo; Kriechbaum, Manfred; Uhlig, Frank; Galli, Giancarlo; Martinelli, Elisa
Abstract: Amphiphilic tetrafluorostyrene monomers (EFSn) carrying in the para position a polyethyleneglycol (PEG) chain with varied lengths (n = 3–13) were synthesized and polymerized by ARGET-ATRP to obtain the corresponding amphiphilic homopolymers pEFSn-x with controlled and tailored polymerization degrees (x = 8–135). All polymers presented a reversible thermoresponsive LCST-type behavior, in water/methanol mixture when n ≤ 4 or in pure water when n ≥ 8, with a cloud point (Cp ) temperature in the range 30–40 °C strictly dependent on the length of the PEG side chain. Combined small angle X-scattering (SAXS) and dynamic light scattering (DLS) measurements were used to study the self-assembly behavior in water of the water-soluble amphiphilic homopolymers. SAXS confirmed the formation of compact-sized and spherical single-chain self-folded nanostructures below Cp, that generally presented small hydrodynamic diameters ( D h  ≤ 11 nm) as proven by DLS analysis. Above Cp, much larger multi-chain aggregates were formed ( D h  ≥ 800 nm), that reversibly turned back to collapsed nanostructures on cooling below the Cp temperature. By contrast, the polymers were not able to self-assemble in THF or DMF solutions, in which they adopted conventional random coil conformations. Graphical abstract: Image 1 Highlights: Amphiphilic PEG-modified fluorinated styrene homopolymers were synthesized by ARGET-ATRP. Polymers showed a reversible LCST-type behaviour with a Cp dependent on the PEG length. Water soluble polymers formed in water compact, core-shell unimer micelles below Cp . The spherical unimer micelles presented small hydrodynamic diameters generally ≤11 nm. Unimer micelles collapsed in large multi-chain aggregates above Cp .